A Study on L1 Use in English Classroom: Perception and Practice - Elisabeth Marsella (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2022)
The use of L1 in language learning has become a debate for years. The opponents of L1 use argue that the use of first language (L1) may deprive the exposure of the target language (L2) that will affect learners L2 acquisition. As the consequence, learners must use L2 all the time for learning. However, the proponents say that there is not any evidence showing the use of exclusive L2 makes learners get higher achievement. Instead, the L1 enables learners to notice L2 features, to clear up misunderstanding, to learn vocabulary and grammar faster and to memorize the language. There have been a lot of studies conducted to see the perception of teachers and students on the use of L1 and the practice of L1 use in the classroom. However, few discuss the teacher and student interaction in the framework of IRF (initiation-response-follow up) exchange and Conversation Analysis. The teachers thought that the use of L2 should be used maximally, while students preferred combining L1 and L2 for learning. In the practice, L1 was still constantly used by teachers and students. Teachers usually used L1 for knowledge building and managing classes, while students used L1 for all aspects of learning.